BUMDes Strategies for Successful Banana Planting Programs - Syaharani, Farah Nabilah; Choiriyah, Ilmi Usrotin (Indonesian Journal of Cultural and Community Development, 2024)
General Background: Village-Owned Enterprises (BUMDes) are essential for enhancing local economies through agricultural initiatives. Specific Background: In Krembung Village, Sidoarjo Regency, a banana planting program has been implemented to improve productivity and income. Knowledge Gap: However, challenges like high seedling mortality and inadequate practices hinder success. Aims: This study analyzes BUMDes strategies in executing the banana program, focusing on community involvement and resource management. Results: While strength and progress indicators are optimal, the value aspect is suboptimal due to significant seedling losses. Community support for banana cultivation has been strong. Novelty: The research highlights practical challenges and strategic approaches in managing BUMDes agricultural programs. Implications: Findings emphasize the need for better resource allocation and community engagement to enhance agricultural initiatives, providing insights for improving BUMDes operations and promoting sustainable rural development. Highlights: Community Involvement: Strong local support is crucial for the success of the banana planting program. Resource Management: Effective allocation and management of resources are necessary to mitigate seedling mortality. Strategic Approaches: Implementing targeted strategies can enhance agricultural productivity and economic benefits for the village. Keywords: BUMDes, Banana Planting, Community Engagement, Agricultural Productivity, Village Potential